Morphometric and phaneroptic characteristics of creole goats in the dry forest of Peru - Acosta Granados, Irene Carol; Carrero Flores, Jhonatan Enrique; Acosta Vidaurre, Rogelio; Cruz Luis, Juancarlos Alejandro; Ruíz Chamorro, José Antonio (UNEMAT, 2025)
The study aimed to describe morphometric and phaneroptic parameters in goat herds from the northern region of Lambayeque, Peru. A total of 295 goats over two years old, without evidence of crossbreeding with specialized breeds, were used. For each animal, 19 morphometric and eight phaneroptic measurements were recorded, and zoometric indices were calculated using a scale, measuring tape, and zoometric stick. This was performed using R software version 4.3.1. The results showed an average live weight of 41 ± 7.5 kg and a proportionality index of 99.6, highlighting their suitability for meat or dual-purpose production (IDT: 13.4, ICO: 88.7), adapted to the local environment. Regarding phaneroptic characteristics, monochromatic coat colors predominated in 55.6% of the animals, 43.7% were hornless (72.7% of the horns observed were parallel), 20.7% had beards, and 10.5% presented wattles. Additionally, 14.7% had supernumerary teats, and 46% of males displayed testicular bifurcation. In conclusion, the Creole goat of the Dry Forest in northern Peru is medium-sized, with robust limbs and a meat-production aptitude, as reflected by the proportionality index. It is also characterized by predominantly dark coats and parallel horns when present. These features demonstrate their adaptation to this environment and their potential for meat production.